Taxonomia, variação morfológica e distribuição geográfica das espécies do grupo Hyla circumdata (Cope, 1870) (Amphibia, Anura, Hylidae) - Napoli, Marcelo Felgueiras (2000)
The Hyla circumdata species group currently comprises eleven species, which are distributed over mountain stream habitats in Atlantic Tropical Forest, with altimetric range over 500 m. This group is diagnosed by transverse bands on the posterior surface of thighs and hypertrophied prepollex. However, this diagnosis comprises other groups, as H. boans and H. martinsi species groups. The analysis of external morphology of adult specimens, including fifteen morphometric characters, tadpoles, vocalization, natural history, and geographic distribution, revealed considerable intra- and interpopulation variation of some taxa, including geographic gradients of variation not easy to understand. Morphological characters, osteology, and natural history were added to the original diagnosis of H. circumdata species group, in order to avoid superpositions with allied species groups. Hyla ibitiguara was removed from the H. circumdata species group by general morphology and habits, and grouped with H. pseudopseudis Miranda-Ribeiro, 1937 and H. saxicola Bokermann, 1964. Hyla martinsi Bokermann, 1964 and H. langei Bokermann, 1965 were grouped together, characterized by developed humeral crest and bifid prepollex. Hyla clepsydra A. Lutz, 1925 and H. claresignata Lutz and Lutz, 1939 were grouped together, characterized by distinct external characters in adults and stream-adapted tadpoles. The H. pulchella and H. alvarengai species groups were not combined with H. circumdata species group, mainly by differences in coloration, externai morphology and habits. Thus, the H. circumdata species Group comprises the following species: H. astartea, H. carvalhoi, H. circumdata, H. gouveai, H. hylax, H. ibitipoca, H. izecksohni, H. luctuosa, H. nanuzae and H. sazimai; moreover, four new taxa were proposed for the group, located at Mantiqueira setentrional, Serra da Bocaina, Serrado Ibitipoca, and northem Minas Gerais. The pattem of geographic distribution of species of the H. circumdata group correlates well with biogeographic predictions cited in herpetological literature for “groups that occurred in the Atlantic Forest Domain throughout a long period of evolution”, which may be correlated with uplifting of coastal mountains throughout the Cenozoic.